2020
DOI: 10.1101/2020.12.10.419788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The apicoplast link to fever-survival and artemisinin-resistance in the malaria parasite

Abstract: BackgroundThe emergence and spread of Plasmodium falciparum parasites resistant to front-line antimalarial artemisinin-combination therapies (ACT) threatens to erase the considerable gains against the disease of the last decade. We developed a new large-scale phenotypic screening pipeline and used it to carry out the first large-scale forward-genetic phenotype screen in P. falciparum to identify genes that allow parasites to survive febrile temperatures.ResultsScreening identified more than 200 P. falciparum m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The free radicals and ROS generated from activation of ART can damage parasite DNA ( Gopalakrishnan and Kumar, 2015 ), and the mutations in genes associated with DNA synthesis, mismatch repair, and oxidative damage response in ART-resistant parasites in the GMS bestow these parasites a greater ability to deal with DNA damage caused by ART exposure ( Miotto et al, 2013 ; Takala-Harrison et al, 2013 ; Xiong et al, 2020 ). A recent forward genetic, phenotypic screen for heat-shock response genes using the piggyback transposon system demonstrated that the malaria parasite uses a shared crisis-response mechanism (upregulated UPR and downregulated endocytosis and ubiquitination) to relieve the build-up of damaged proteins from different stresses such as febrile temperatures and drugs ( Zhang et al, 2020 ).…”
Section: Art Resistance: the Unusual Phenotype And Underlying Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…The free radicals and ROS generated from activation of ART can damage parasite DNA ( Gopalakrishnan and Kumar, 2015 ), and the mutations in genes associated with DNA synthesis, mismatch repair, and oxidative damage response in ART-resistant parasites in the GMS bestow these parasites a greater ability to deal with DNA damage caused by ART exposure ( Miotto et al, 2013 ; Takala-Harrison et al, 2013 ; Xiong et al, 2020 ). A recent forward genetic, phenotypic screen for heat-shock response genes using the piggyback transposon system demonstrated that the malaria parasite uses a shared crisis-response mechanism (upregulated UPR and downregulated endocytosis and ubiquitination) to relieve the build-up of damaged proteins from different stresses such as febrile temperatures and drugs ( Zhang et al, 2020 ).…”
Section: Art Resistance: the Unusual Phenotype And Underlying Mechanismsmentioning
confidence: 99%
“…Recent studies also shed light on the significance of mitochondrion and apicoplast in stress response and ART resistance ( Mok et al, 2021 ; Zhang et al, 2020 ). Mitochondria are identified as one of the cellular targets of ARTs ( Wang et al, 2010 ) and mitochondrial activity is critical for the survival and regrowth of dormant parasites after DHA exposure ( Peatey et al, 2015 ).…”
Section: Art Resistance: the Unusual Phenotype And Underlying Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific binding to the G-box is conferred by D1 10 , but activation of these genes during HS strictly requires D3, which is not capable of binding DNA in vitro 10 and likely participates in protein-protein interactions or dimerization 34 . Other components of the protein folding machinery necessary for HS survival [35][36][37] are constitutively expressed or induced later, but the rapid PfAP2-HS-driven response is essential to avoid irreversible damage, as parasites lacking D3 or the full protein fail to survive HS. While PfAP2-HS is not evolutionarily related with HSF1 5,8 , the conserved master regulator of the HS response from yeast to mammals, it appears to play an analogous role.…”
mentioning
confidence: 99%